Bridging Cultural Barriers through AI: Toward a Scalable Model of Christian Leadership Multiplication - Yuco Aldelina; Verdi Madison Sjahlendra; Reiko Yona Dumais; Manlian Ronald. A. Simanjuntak (Scriptura Indonesia, 2026)
The global mandate of leadership multiplication within the Missio Dei framework faces a systemic crisis where the demand for trained leaders outpaces the capacity for spiritual formation, primarily due to linguistic barriers on the Unreached and Unengaged People Group (UUPG) regions. This study explores the role of Artificial Intelligence (AI) as a strategic accelerator to transcend these barriers through a scalable model for Christian leadership formation. Employing a qualitative conceptual approach, the research utilizes theological-sociological analysis and the DELTA ethical framework while evaluating technical implementation data from the IFGF College Artificial Intelligence (AI) project. The findings reveal that AI integration achieved a thirty-fold acceleration in leadership multiplication, successfully adapting theological curricula into 33 languages in just 1.5 years. However, the discussion highlights critical risks such as the